THE EFFECT OF DIFFERENT TYPES OF COMMENTS (PRAISE, SUGGESTION, AND CRITICISM) ON STUDENTS’ WRITING ACHIEVEMENT - Nanik Sri Rahayu (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
Teacher’s comments as a respond to the students’ draft has an important effect on students writing motivation and achievement during the teaching and learning process in writing. These comments or the teacher reply for the students’ draft are usually waited by the students as it is assumed as a two- way communication during completing the final draft. However, many students may have different responds in accommodating these comments. This study investigated whether praise, suggestion, and criticism as teacher’ comments have significant effects on the students writing paragraph achievement. Through a quasi-experimental design using quantitative methods for students in the third semester of IAIN Tulungagung's English Department, the research shows that there are significant differences in writing paragraph scores between students taught before and after using different types of comments. In addition, among these three strategies, the suggestion gave more improvement than the other two types of comments.